2019
DOI: 10.26502/jcsct.5079038
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Latissimus Dorsi Mini-Flap in Partial Breast Reconstruction

Abstract: Introduction: The cosmetic drawbacks of breast conserving surgery are asymmetry, nipple or skin retraction, and volume loss with unsatisfactory cosmetic outcome. The principle of Latissimus dorsi mini-flap (LDMF) is to use part of the Latissimus dorsi (LD) muscle as volume replacement to large breast defect up to 20 -30 % of the breast volume.Purpose: To evaluate (LDMF) as a volume replacement to large breast defect after wide local excision in different breast quadrants and the benefit of using this procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…16 A study by Ibraheem MH et al stated that the cosmetic drawbacks of breast-conserving surgery are asymmetry, nipple or skin retraction, and loss of volume, which results in unsatisfactory cosmetic results. 11 LD flap is an essential reconstruction method of choice due to its stability and flexibility as an autologous flap. However, some of the disadvantages of the flap are associated with additional donor sites with scarring and potential morbidity.…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…16 A study by Ibraheem MH et al stated that the cosmetic drawbacks of breast-conserving surgery are asymmetry, nipple or skin retraction, and loss of volume, which results in unsatisfactory cosmetic results. 11 LD flap is an essential reconstruction method of choice due to its stability and flexibility as an autologous flap. However, some of the disadvantages of the flap are associated with additional donor sites with scarring and potential morbidity.…”
Section: Original Articlementioning
confidence: 99%
“…In a study by Ibraheem MH et al, about 15 patients had donor site seroma. 11 The study result by Lee JS et al, who performed breast reconstruction with LD flap in January 2014 until June 2018 with 275 cases, stated that there were 3 cases of hematoma developed after breast reconstruction with LD flap. 17 Although previous studies had indicated seroma as the most common complication, the incidence of hematoma in a few years after surgery is rarely reported late.…”
Section: Original Articlementioning
confidence: 99%
“…There are only few papers reported on the practicability of this technique in treating women with a large tumor. 14,15 Therefore, we conducted a study to assess the oncological clearance and cosmetic outcomes of partial breast reconstruction using a LDMF following a BCS for various breast pathologies.…”
Section: Introductionmentioning
confidence: 99%